Optimalisasi Penegakan Hukum dalam Mengurangi Kepemilikan Tanah Absentee demi Terwujudnya Keadilan Sosial - Widagdo, Hairul Dharma (Lembaga Kajian, Penelitian dan Pengembangan Mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Distribution of agricultural land is closely linked to the landreform program. One of the objectives of this program is to increase the productivity of agricultural land. This is an effort of the Government in providing justice for the community in accordance with the purpose of the state. One of the aims of the state is to promote the common prosperity. This writing uses the type of empirical legal research with the approach statute approach and conseptual approach, which aims to explore the problem of absentee land that is rife owned by the community in several areas, especially in the city of Blitar. In addition, to provide solutions and preventive measures to overcome absentee land ownership. Distribusi tanah pertanian berhubungan erat dengan program landreform. Salah satu tujuan dari program ini adalah peningkatan produktifitas lahan pertanian. Hal ini merupakan upaya Pemerintah dalam memberikan keadilan bagi masyarakat sesuai dengan tujuan negara. Salah satu tujuan negara yaitu untuk memajukan kesejahteraan umum. Penulisan ini menggunakan jenis penelitian hukum empiris dengan pendekatan statute approach dan conseptual approach, yang bermaksud menggali permasalahan tentang tanah absentee sedang marak di beberapa daerah khususnya di Kota Blitar. Selain itu, guna memberikan solusi dan langkah preventif untuk mengatasi kepemilikan tanah absentee.